International banking and liquidity risk transmission: Lessons from across countries - Claudia M. Buch; Linda Goldberg (Deutsche Bundesbank, 2014)
Activities of international banks have been at the core of discussions on the causes and effects of the international financial crisis. Yet, we know little about the actual magnitudes and mechanisms for transmission of liquidity shocks through international banks, including the reasons for heterogeneity in transmission across banks. The International Banking Research Network (IBRN), established in 2012, brings together researchers from around the world with access to micro-data on individual banks to analyze issues pertaining to global banks. This paper summarizes the common methodology and results of empirical studies conducted in 11 countries to explore liquidity risk transmission. Among the main results is, first, that explanatory power of the empirical model is higher for domestic lending than for international lending. Second, how liquidity risk affects bank lending depends on the whether the banks are drawing on official sector liquidity facilities. Third, liquidity management across global banks can be important for liquidity risk transmission into lending. Fourth, there is substantial heterogeneity in the balance sheet characteristics that affect banks' responses to liquidity risk. Overall, bank balance sheet characteristics matter for differentiating lending responses across banks mainly in the realm of cross-border lending.
Keywords: G01; F34; G21; 330; International banking; liquidity; transmission; central bank liquidity; uncertainty; regulation; crises